Whole Body Coordination and Knee Movement Control During Five Rehabilitation Exercises. Issue 6 (2nd November 2017) - van Deursen, Robert W. M.; Button, Kate; Roos, Paulien E.
ABSTRACT: Knee rehabilitation exercises to improve motor control, target movement fluency, and displacement variability. Although knee movement in the frontal plane during exercise is routinely assessed in clinical practice, optimal knee control remains poorly understood. In this study, 29 healthy participants (height: 1.73 ± 0.11 m, mass: 73.5 ± 16.4 kg, age: 28.0 ± 6.9 years) performed 4 repetitions of 5 rehabilitation exercises while motion data were collected using the VICON PlugInGait full-body marker set. Fluency and displacement variability were calculated for multiple landmarks, including center of mass (CoM) and knee joint centers. Fluency was calculated as the inverse of the average number of times a landmark velocity in the frontal plane crossed zero. Variability was defined as the standard deviation of the frontal plane movement trajectories. CoM fluency and displacement variability were significantly different between tasks ( p < .001). CoM displacement variability was consistently smallest compared to the constituent landmarks ( p < .005). This was interpreted as a whole body strategy of compensatory variability constraining CoM frontal plane movement. Ipsilateral knee fluency ( p < .01) and displacement variability ( p < .001) differed substantially between tasks. The role of the weight-bearing knee seemed dependent on task constraints of the overall movement and balance, as well as constraints specific for knee joint stability.